Kajian Saat Panen Rumput Pakchong Sebagai Hijauan Pakan Ternak Sapi Perah - Mahfud, Mohammad Cholil (Universitas Islam Kadiri, 2024)
Pakchong grass is widely planted by farmers in Tutur District as forage for dairy cattles, but the right harvest time to get quality forage is not yet known. Harvest age greatly influences the quality and production of forage for livestock. This study aims to find out the right time to harvest forage so that quality forage can be obtained as feed for dairy cattle. The research was carried out in Mesagi Gardens, Wonosari village, Tutur District, through an experiment using a Randomized Group Design (RAK). The treatment is the harvest age of Pakchong grass, consisting of: (a) harvest age 40-45 days (P1); (b) harvest aged 55-60 days (P2); and (c) harvest aged 70-75 days (P3). Each treatment was repeated nine times (U1-U9). The study began after the Pakchong grass on the organic land was harvested. The land is then fertilized with organic fertilizer (slurry) at 10 tones/ha. A total of 27 experimental plots were created, each measuring 2 m2 by attaching raffia rope tied to bamboo which was stuck into the ground. Each experimental plot was labeled with a treatment. Pakchong grass is allowed to grow, and harvested according to treatment, by cutting the base of the stem to a height of about 5 cm above the ground surface. Based on the forage harvest and preferences of dairy cows, proximate content and production and quality of organic milk, it was concluded that the highest quality Pakchong grass as forage for dairy cows is harvested at the age of 55-60 days.